Factor VIII Bypassing Activity (FEIBA) assays: standardization and development of the 1st NIBSC Working Standard for FEIBA – results from a collaborative study. (23rd November 2012) - Raut, S.; Daniels, S.; Gärtner, P.; Hunfeld, A.; Leitner, M.; Hockley, J.; Heath, A.
Summary Factor‐Eight‐Inhibitor‐Bypassing‐Activity (FEIBA) is a bypassing‐agent used to control spontaneous bleeding or cover surgical interventions in Haemophiliacs who develop neutralizing antibodies against FVIII/FIX. The market lot‐release of FEIBA is dependent on specific clot‐based assays, carried out by both the manufacturer and regulatory authorities, relative to manufacturer's in‐house standards, which are produced on a small‐scale and are replaced frequently. We sought to standardize the FEIBA assay by developing a FEIBA primary standard which would be internationally available in sufficiently large quantities, with a predicted lifetime of many years. A collaborative study involving the manufacturer and three regulatory authorities, was carried out in which a candidate material, sample B (06/172), was calibrated by assays relative to the manufacturer's in‐house FEIBA standards (C and D). All laboratories used their routine validated methods (16 APTT‐assays, 8 ACTIN‐FS‐assays and 27 DAPTTIN‐assays). Intra‐laboratory geometric coefficients of variation (GCVs) for candidate B ranged from 3% to 29% (GCVs <9% from majority of labs). Assessment of inter‐laboratory variability gave overall GCV values of 6.9% and 4.4% relative to standards C and D, respectively, for all methods. There was good agreement in potency estimation between laboratories using each of the three methods, with the overall potencies by the three methods differing by less than 10% of the overall mean, giving an overall combined potency of 28.0 units per ampoule. All participants agreed that candidate B (06/172) be established as the 1st NIBSC Working Standard for FEIBA with an assigned potency of 28.0 units per ampoule, based on combined results for both methods, relative to either standard C or D.